Comparison of the Prognostic Outcome between High-Grade Ovarian Sertoli-Leydig Cell Tumors (SLCTs) and Low-Grade SLCTs - Eoh, Kyung Jin; Park, Junsik; Kim, Hye Min; Lee, Maria; Kim, Young Tae (Yonsei medical journal, 2021)
The purpose of the current study was to compare prognostic outcomes between patients with high-grade ovarian Sertoli-Leydig cell tumors (SLCTs) and those with other low-grade SLCTs. We retrospectively reviewed medical records for 24 patients pathologically diagnosed with SLCTs between 2006 to 2019 at two institutions. The patients were grouped according to pathological grade: SLCT was classified as grade 1, well differentiated; grade 2, intermediated differentiated; or grade 3, poorly differentiated (Meyer's classification). Statistical analysis was performed to compare survival outcomes according to pathological grade. The median patient age was 42.5 years (range 16-75). Eighteen patients (75%) were International Federation of Gynecology and Obstetrics stage I, and none were diagnosed in stage IV. Nine patients (37.5%) were grade 3, and 15 patients (63.5%) were grades 1-2. When comparing clinical baseline characteristics of the grade 1-2 group with those of the grade 3 group, only serum CA125 level at diagnosis was significantly higher in the grade 3 group (38.34 vs. 382.29, =0.002). Five patients experienced recurrence of grade 3 disease, while no recurrence was reported in grade 1-2 disease. Four of the five recurrent patients died. In result, grade 3 ovarian SLCT showed significantly poorer prognosis than grade 1-2 disease (overall survival, hazard ratio=14.25, 95% confidence interval=1.881-108.0; log-rank =0.010). Our findings were consistent with the concept that patients with stage I/grade 1-2 tumors have a good prognosis without adjuvant chemotherapy. Since grade 3 ovarian SLCT appears to be relatively more fatal than grade 1 or 2, patients with grade 3 SLCT might require more aggressive surgical intervention and post-treatment surveillance.